Sound environmental impact resulting from the operation of aircraft at Santos Dumont Airport – Rio de Janeiro - Costa, Jordana; Júnior, Edson Carvalho; Garavelli, Sérgio; Maroja, Armando (Seven Editora, 2023)
The operation of aircraft produces negative environmental externalities, such as air pollution and aeronautical noise that impacts the areas near airport sites, becoming a major source of conflicts between communities and airport operators. Noise discomfort from exposure to airborne noise affects health, quality of life and sleep. Thus, it is important to conduct research that seeks to evaluate the impact of aeronautical noise in the surroundings of airports. Thus, in the present work the sound impact caused by aeronautical noise in areas surrounding Santos Dumont airport (SBRJ) in the State of Rio de Janeiro was evaluated. The methodology was based on simulations of noise curves in the acoustic metric DNL (day-night level) using the INM 7.0d software. The input data required for the simulations were provided by INFRAERO for the year 2016. With the noise curves, acoustic maps were elaborated with the aid of the  QGIS 2.18 software. The population exposed to air noise in different noise curves was also determined. In addition, a comparison was made between the methodologies currently used in Brazil and in the European Community to determine the percentage of people who were bothered (%I) and highly bothered (%AI) in the different noise curves. The results indicate that the percentage of disturbed in each noise curve is small when related to the number of inhabitants per neighborhood and it is concluded that for a better evaluation of the impact of aeronautical noise, RBAC 161 (2013) can be complemented with the calculation of the exposed population with its percentages of bothered and highly bothered people. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-049